Pancreatitis and calcium signaling - Petersen, Ole (Henry Stewart Talks, 2007)
Normal Calcium signaling events in pancreatic acinar cells, Hyperstimulation as a cause of sustained global elevation of the cytosolic [Calcium], Calcium-dependent vacuolization and Calcium-dependent protease activation, Bile acids causing sustained global Calcium signals and necrosis, Calcium-dependent necrosis evoked by non-oxidative alcohol metabolites (fatty acid ethyl esters and fatty acids) but not by alcohol or acetaldehyde, The mechanism of action of fatty acid ethyl esters and fatty acids, The mildly protective effect of coffee (caffeine), A model for the initiation of alcoholic pancreatitis